Stifle synovial cyst in a Labrador Retriever with concurrent cranial cruciate ligament deficiency - Franklin, A. D.; Havlicek, M.; Krockenberger, M. B. (Veterinary and Comparative Orthopaedics and Traumatology, 2011)
A seven-year-old Labrador Retriever dog was presented with the complaint of chronic left hindlimb lameness. A diagnosis of partial rupture of the left cranial cruciate ligament with concurrent cranio-medial synovial cyst formation was made. This cystic structure was assumed to be communicating with the stifle joint. There was no evidence of a meniscal tear, but superficial fibrillation of the axial border was present. Surgical excision of the cyst with concurrent treatment of the cranial cruciate ligament deficiency by tibial tuberosity advancement was performed with a successful outcome. Whilst commonly encountered in humans, synovial cysts are uncommon in dogs. To the authors’ knowledge this is the first reported case of synovial cyst formation in the stifle of a dog.
Keywords: Stifle; synovial cyst; cranial cruciate ligament; meniscus; arthrotomy